Arachidonic acid closes innexin/pannexin channels and thereby inhibits microglia cell movement to a nerve injury. Issue 8 (18th June 2013) - Samuels, Stuart E.; Lipitz, Jeffrey B.; Wang, Junjie; Dahl, Gerhard; Muller, Kenneth J.
ABSTRACT Pannexons are membrane channels formed by pannexins and are permeable to ATP. They have been implicated in various physiological and pathophysiological processes. Innexins, the invertebrate homologues of the pannexins, form innexons. Nerve injury induces calcium waves in glial cells, releasing ATP through glial pannexon/innexon channels. The ATP then activates microglia. More slowly, injury releases arachidonic acid (ArA). The present experiments show that ArA itself reduced the macroscopic membrane currents of innexin‐ and of pannexin‐injected oocytes; ArA also blocked K+‐induced release of ATP. In leeches, whose large glial cells have been favorable for studying control of microglia migration, ArA blocked glial dye‐release and, evidently, ATP‐release. A physiological consequence in the leech was block of microglial migration to nerve injuries. Exogenous ATP (100 µM) reversed the effect, for ATP causes activation and movement of microglia after nerve injury, but nitric oxide directs microglia to the lesion. It was not excluded that metabolites of ArA may also inhibit the channels. But for all these effects, ArA and its non‐metabolizable analog eicosatetraynoic acid (ETYA) were indistinguishable. Therefore, ArA itself is an endogenous regulator of pannexons and innexons. ArA thus blocks release of ATP from glia after nerve injury and thereby, at least in leeches, stops microglia at lesions. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 73: 621–631, 2013